Remote sensing of mangroves using unmanned aerial vehicles: current state and future directions. Issue 2 (4th May 2021) - Zimudzi, Edward; Sanders, Ian; Rollings, Nicholas; Omlin, Christian W.
ABSTRACT: Mapping and identification of mangrove tree species have always played a crucial role in mangrove ecosystem conservation efforts, and several attempts have been made using remote sensing techniques for the acquisition of images and machine learning techniques for image processing with various levels of success. Remote sensing, combined with machine learning techniques have demonstrated a high potential to map and identify these ecosystems. In this research, we have conducted a systematic study with the goal of collecting all relevant research on mangrove species mapping and species identification using unmanned aerial vehicles (UAVs). Our objective is to understand current research topics, addressing the methods and techniques used for mangrove image data analysis, research gaps, and the challenges and future directions regarding mangrove species mapping and identification from remote sensing images acquired using UAVs. This will assist future research directions in managing these most threatened and vulnerable mangrove ecosystems.